Aspects of Behavioral Diversity in Society: Mysticism, Puritanism, the Profane, and Ritual - Biari, Dina Audina Hasan (Maliki Interdisciplinary Journal, 2025)
Behavioral diversity in society reflects a dynamic interplay of social, spiritual, and cultural values. This article explores the wisdom behind differences in religious behavior using a multidisciplinary approach, drawing from the theories of Max Weber and Emile Durkheim. Four main dimensions of wisdom are examined: (1) the individual's connection to the Divine through mystical and religious experiences; (2) the development of mental and emotional self-control through mystical, puritanical, ritual, and profane values; (3) the strengthening of social solidarity through interaction and tolerance in diversity; and (4) the structured advancement of civilization through rational systems and collective values. Diversity is not treated as a threat, but as a resource for spiritual and social growth. This study shows that behavioral differences hold great potential in shaping an inclusive, emotionally resilient, and progressively civilized society. The research employs a qualitative-descriptive method based on literature review and sociological perspectives.